2020
DOI: 10.1111/pops.12680
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Partisanship? Evidence that In‐Party Scandals Increase Out‐Party Hostility

Abstract: Contemporary U.S. politics is characterized by polarization and interpartisan antipathy. This is accompanied by a media landscape saturated with coverage of political scandals. Applying a social identity perspective, we examined whether exposure to scandals that threaten partisan's moral group image (i.e., in‐party scandals), may motivate defensive hostility against opposing partisans. Across three experiments we exposed U.S. partisans to scandals attributed to either in‐party or out‐party politicians. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Regarding affective polarization, most studies found that traditional media predicted increased affective polarization. Reading a news article about an in-party scandal (Rothschild et al,2021), having a highly diverse media environment alongside exposure to negative political ads (Lau et al, 2017), being exposed to likeminded (vs. cross-cutting) news media (Levendusky, 2013), and incivility on news media from out-party sources (Druckman et al, 2019), were associated with increased affective polarization. However, some researchers' experimental manipulations decreased affective polarization.…”
Section: Media Effectsmentioning
confidence: 99%
“…Regarding affective polarization, most studies found that traditional media predicted increased affective polarization. Reading a news article about an in-party scandal (Rothschild et al,2021), having a highly diverse media environment alongside exposure to negative political ads (Lau et al, 2017), being exposed to likeminded (vs. cross-cutting) news media (Levendusky, 2013), and incivility on news media from out-party sources (Druckman et al, 2019), were associated with increased affective polarization. However, some researchers' experimental manipulations decreased affective polarization.…”
Section: Media Effectsmentioning
confidence: 99%
“…As an outcome of social sorting, partisans are now more distinct from each other demographically than in the past, with fewer cross‐cutting identities to stabilize interparty relations (Mason, 2016, 2018; Mason & Wronski, 2018). Growing partisan social dissimilarity has exacerbated an “us versus them” mentality resulting in greater negative affect toward partisan rivals whose disputes are not just partisan but also extend to related claims concerning group respect and status (Mason, 2015, 2018; see also Ahler & Sood, 2018; Rothschild, Keefer, & Hauri, 2020). From this perspective, identity threats are a key ingredient in the development of affective polarization.…”
Section: Policy and Group‐based Models Of Affective Polarizationmentioning
confidence: 99%
“…El contenido que presenta el conflicto político entre partidos, fomentaría la hostilidad partidista a través del refuerzo de la identidad partidista por amenaza externa y en consecuencia la polarización afectiva a través del consumo de noticias como un factor intermediario entre ambos (McLaughlin, 2018). En este aspecto, los escándalos políticos son también un momento de saliencia de la identidad partidista y de aumento de la hostilidad hacia el out-group pero no reduce la favorabilidad hacia el in-group (Rothschild et al, 2021).…”
Section: ¿Qué Es Lo Que (De)polariza Afectivamente?unclassified